Penguatan petani kecil dalam mendukung ketahanan pangan nasional - Abidin, Jamaludin Zainal (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Food security is a crucial issue in the world today. The increasing demand for food is driven by the continuously growing global population. Food requirements in developing countries are projected to increase by 60% in 2030 and double by 2050. Indonesia is one of the countries with significant potential to meet global food needs. However, Indonesia has not been able to maximize the productivity of its agricultural land, leading to insufficient domestic food supply. On the other hand, the condition of small farmers in Indonesia remains concerning. Small farmers in Indonesia are still part of a vulnerable community due to the low income derived from agriculture.In this research, the analysts conducted an examination related to strengthening small farmers to support national food security. The research employed a qualitative methodology based on a literature review of previous studies. The discussion in this study presents several policy recommendations, including optimizing plantation land integrated with agriculture through the agroforestry concept. Another policy suggestion is to focus on supporting small farmers in gaining access to agricultural knowledge and technology through mentoring programs. The government also needs to stimulate millennials to contribute directly to the agricultural sector, as evidenced by the role of millennial farmers in enhancing agricultural productivity and competitiveness. Finally, the Indonesian government should facilitate access to funding for small farmers and promote the development of local food alternatives such as corn, cassava, and sorghum, aiming to enhance national food security and contribute to global food resilience.